Incidence and identification of microfibers in ocean waters in Admiralty Bay, Antarctica - Absher, Theresinha Monteiro; Ferreira, Silvio Luiz; Kern, Yargos; Ferreira, Augusto Luiz; Christo, Susete Wambier; Ando, Rômulo Augusto (Environmental science and pollution research international, 2019)
Antarctic pristine environment is threatened by the presence of microplastics that occur in a variety of shapes and sizes, from fibers to irregular fragments. The aim of this study is to assess the abundance, distribution, and the characterization of the microfibers in zooplankton samples found in ocean waters in Admiralty Bay, Antarctica. The samples were collected at five points in Admiralty Bay during the XXIX Brazilian Antarctic Expedition in the austral summer of 2010–2011. A total of 603 microfibers were collected in 60 samples, with an average abundance of 2.40 (± 4.57) microfibers 100 m −3 . Microfiber size ranging from ca. 10 to 22 μm in diameter of various lengths and colors (blue, red, black, and clear) was collected and characterized by scanning electron microscopy (SEM) and Raman spectroscopy. Most of these microfibers were entangled in various different zooplankton species and were identified as polymers composed mostly by polyethyleneglycols, polyurethanes, polyethylene terephthalates, and polyamides. The presence of such microfibers may cause the loss of biodiversity in the Antarctic continent, and the results presented herein can contribute to a better understanding of the impact caused by them within the food chain and human health. Graphical Abstract ᅟ